Perancangan Sistem Informasi Penjualan Online Pada Keler Bouquet Dengan Metode Prototype - Widya, Sagita; Sembiring, Falentino (STIKOM Tunas Bangsa Pematangsiantar, 2023)
Online stores can make it easy for businesses to reach a wider market. Especially for small businesses that don't have physical stores, they can sell their products through online stores, so they can increase their sales turnover. The purpose of this research is to design an online sales information system that can increase customer satisfaction and reduce sales failures. This study uses the design thinking method which focuses on problem solving by following the steps of observation and interviews, problem definitions, ideas and prototyping. The result of this research is an online sales information system prototyping that will increase customer satisfaction with features such as an easy ordering process, secure payments, and fast delivery. In addition, this system will also reduce sales failures with features such as updated product stock and detailed product information.